Case Report: Frontalis sign for early bedside consideration of impending uncal herniation - Munakomi, Sunil (F1000Res, 2016)
It is prudent to have early diagnosis and timely management of uncal herniation for better management of neurosurgical patients. There are several clinical and radiological armamentariums that aid in early recognition of the condition. Through this case report, we try to highlight a simple bedside clinical sign that can be a valuable adjunct in early recognition of the impending uncal herniation especially in scenarios wherein it is difficult to assess the pupillary size and reactivity correctly. The improvement in the sign also confirms the resolution of the mass effect in the postoperative period. This is especially helpful for doctors working in the periphery or in resource restrained areas, for a timely referral of the patient to tertiary centre.